2023
DOI: 10.1186/s13620-023-00235-y
|View full text |Cite
|
Sign up to set email alerts
|

Association between body condition score, testicular haemodynamics and echogenicity, nitric oxide levels, and total antioxidant capacity in rams

Abstract: Higher body fatness adversely affects metabolic and hormonal homeostasis. The present work aimed to evaluate the association between body condition score (BCS) and haemodynamic pattern and echogenic appearence of the testes as well as nitric oxide (NO) levels and total antioxidant capacity (TAC). For that, fifteen Ossimi rams were blocked according to their BCS into a lower BCS group (L-BCS:2–2.5; n = 5), medium BCS group (M-BCS:3–3.5; n = 5), and higher BCS group (H-BCS:4–4.5; n = 5). Rams were examined for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…In the present study, E2 concentrations were negatively associated with the values of both the RI and PI of the OA and MUA. Similarly, strong correlations between Doppler indices of testicular hemodynamics and E2 concentrations were reported in goats [47,48], rams [32,33], buffalo bulls [3], and stallions [45]. Results of the present study indicated an associative relationship between E2 and Doppler indices, an observation deemed important, but there was no elucidation of the underlying mechanism for E2 action.…”
Section: Discussionsupporting
confidence: 42%
See 1 more Smart Citation
“…In the present study, E2 concentrations were negatively associated with the values of both the RI and PI of the OA and MUA. Similarly, strong correlations between Doppler indices of testicular hemodynamics and E2 concentrations were reported in goats [47,48], rams [32,33], buffalo bulls [3], and stallions [45]. Results of the present study indicated an associative relationship between E2 and Doppler indices, an observation deemed important, but there was no elucidation of the underlying mechanism for E2 action.…”
Section: Discussionsupporting
confidence: 42%
“…An E2 (E2-17β) assay was performed using a competitive type of ELISA (DRG kits, Marburg, Germany), with a sensitivity of 9.8 pg/mL [31]. Nitric oxide (NO) was determined colorimetrically using a nitric oxide kit (Bio-diagnostics, Giza, Egypt) with a sensitivity of 0.24 µmol/L [32,33].…”
Section: Blood Sampling and Assessment Of E2 And No Concentrationsmentioning
confidence: 99%
“…Ultrasonography is considered as a substantial tool for evaluating animal reproductive organs (El-Sherbiny et al, 2023;Samir et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasonography is considered as a substantial tool for evaluating animal reproductive organs (El‐Sherbiny et al, 2023; Samir et al, 2023). Improving uteroplacental hemodynamics is crucial for a stable and growing pregnancy, especially in dams bearing more than one foetus.…”
Section: Discussionmentioning
confidence: 99%